Lesotho : Joint Staff Assessment of the Poverty Reduction Strategy Paper Status Report. (IMF Staff Country Reports; Country Report ;, 2004)
This Joint Staff Assessment reviews the Poverty Reduction Strategy Paper (PRSP) Status Report for Lesotho. The report states that the authorities are in the final stages of completing the PRSP and expect to submit it to the Cabinet for approval by mid-October and to the Bank and the IMF by mid-November 2004. Consultations with community-based working and thematic groups were concluded by mid-2003. Subsequently, the authorities carried out detailed exercises regarding costing, development of performance indicators, and document preparation.